(untitled) (Jurnal De Jure Muhammadiyah Cirebon, 2019)
The purpose of mediation is not just to end the dispute, but also to build the sincerity and willingness of the parties without anyone feeling defeated, so that the final mediation estuary outlined in the form of a peace deed is the best choice of the parties based on sincerity. Therefore, the intelligence and expertise of the mediator is very important to resolve disputes between the two parties. This research uses the literature method so that the data collection comes from reading book sources. The result is a successful mediation factor in a divorce case, namely the ability of mediators, sociological and psychological factors, moral and spiritual, the good faith of the parties.